Performance validation of swimsuits by mechanical testing - Buder, J.; Odenwald, S. (Procedia Engineering, 2010)
In this paper a research project for a mechanical test procedure will be presented to detect drag reducing effects of swimsuits. With a newly developed mechanical test design nine swimsuits by six different manufactures were investigated. The mechanical test stand was assembled in a swimming channel and consists of a frame work, a model of an athlete and the force measurement device. Drag force was measured parallel to the stream and recorded at six velocity levels. The collected data and statistics showed the validity of the presented test design.